2008
DOI: 10.1007/s00442-007-0947-0
|View full text |Cite
|
Sign up to set email alerts
|

Movements of wintering surf scoters: predator responses to different prey landscapes

Abstract: The distribution of predators is widely recognized to be intimately linked to the distribution of their prey. Foraging theory suggests that predators will modify their behaviors, including movements, to optimize net energy intake when faced with variation in prey attributes or abundance. While many studies have documented changes in movement patterns of animals in response to temporal changes in food, very few have contrasted movements of a single predator species naturally occurring in dramatically different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…This is consistent with other studies that have suggested that sea ducks can have a great effect on resources (Guillemette et al 1996, Hamilton 2000, Kirk et al 2008). We are confident that ducks were responsible for these effects for a number of reasons.…”
Section: Spring Experiments -Effects Of Predation and Compensationsupporting
confidence: 82%
“…This is consistent with other studies that have suggested that sea ducks can have a great effect on resources (Guillemette et al 1996, Hamilton 2000, Kirk et al 2008). We are confident that ducks were responsible for these effects for a number of reasons.…”
Section: Spring Experiments -Effects Of Predation and Compensationsupporting
confidence: 82%
“…This behaviour creates infrequent exceptions to the stable spatial organisation and adds important knowledge regarding the complexity of spacing behaviour in large mammals in general and wolverines in particular. Territorial fidelity is predicted to be low in habitats where food resources are low, variable and unpredictable and deplete fast (Wauters et al 1995;Kirk et al 2008;Edwards et al 2009). This corresponds to the characterization of wolverine habitat in general (Persson 2005;Inman et al 2012b), and particularly in northern Scandinavia where wolverines are highly dependent on migrating reindeer.…”
Section: Discussionmentioning
confidence: 99%
“…In solitary territorial species, space use is primarily driven by resource competition over access to food or the opposite sex (Sandell 1989;). Territorial fidelity is beneficial because it allows individuals to become familiar with resources in an area, enhancing survival and reproductive success (Switzer 1993;Kirk et al 2008). Furthermore, for species that aggressively defend territories, movement into unfamiliar areas increases mortality risk (Isbell et al 1990;Stamps and Krishnan 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Kirk et al (2008) found that wintering surf scoter distribution patterns in the Malaspina Complex varied considerably through the season; individual surf scoters displayed extensive movements, had large home ranges, and little fidelity to specific foraging sites. Therefore, in order to capture an overall measure of use of each survey polygon, the cumulative numbers of birds were used as an index and corrected for differences in survey polygon size by expressing the cumulative numbers as densities (number of birds per km 2 ).…”
Section: Data Analysesmentioning
confidence: 99%